PENERAPAN PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SD NEGERI 006 TANJUNG BUNGO KECAMATAN KAMPAR TIMUR - ', Sukawati; ', Syahrilfuddin; Marhadi, Hendri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this research is to improve learning outcomes IPS Grade III Elementary School 006 Tanjung Bungo through the use of direct learning. With the research of this class action is expected to provide benefits to various parties, namely: For students are expected to improve learning outcomes in all subjects in general. For those teachers are expected to be a new alternative to increase activity in student learning. This study was conducted in 006 elementary school SDN Tanjung Bungo East Kampar District in class I, while the time the study was conducted in the academic year 2015/2016. As the subjects in this study were teachers and students of class III Elementary School 006 East Tanjung Bungo Kampar District, with a total of 25 students, consisting of 13 men and 12 women. Conclusions from this research is that there is an increase in students' learning outcomes in class III Elementary School 006 Tanjung Bungo using direct instruction. This means that direct learning can improve learning outcomes IPS Elementary School third grade students Tanjung Bungo Kampar District 006 Tanjung Bungo, the initial data acquisition before implemented the use of direct learning, students get an average value of 64.0 in the category enough. Deuteronomy first cycle an average grade of 70.0 in both categories, and the second cycle becomes 83.2 with both categories.Keywords: Learning Outcomes IPS, Direct Learning